CONSTANTIN STERE ȘI FAȚETELE LUI NECUNOSCUTE - COLESNIC, Iurie (BIBLIOPOLIS, 2020)
The author of study, I. Colesnic, highlights some unknown facets of life and work of Constantin Stere (June 1, 1865; Ciripcău, district Soroca, Bessarabia, Russian Empire - June 26, 1936; Bucov Prahova County, Kingdom of Romania), writer, politician, journalist and lawyer. He elucidates moments of his activity as professor, writer’s attempts, his passion for astronomy and gardening, and his compulsion tendency to cause duels.